2017
DOI: 10.3390/jdb5040015
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila as a Model to Study the Link between Metabolism and Cancer

Abstract: Cellular metabolism has recently been recognized as a hallmark of cancer. Investigating the origin and effects of the reprogrammed metabolism of tumor cells, and identifying its genetic mediators, will improve our understanding of how these changes contribute to disease progression and may suggest new approaches to therapy. Drosophila melanogaster is emerging as a valuable model to study multiple aspects of tumor formation and malignant transformation. In this review, we discuss the use of Drosophila as model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 117 publications
(138 reference statements)
0
18
0
Order By: Relevance
“…The role of Hif1α in regulating this switch is of significant interest because, although this transcription factor is classically associated with the response to hypoxia, our study adds to the growing list of examples in which Hif1α remodels cellular metabolism in the context of cell proliferation, activation, and competition, even under normoxic conditions (Miyazawa and Aulehla, 2018). Moreover, our finding is particularly intriguing in light of the fact that Hif1α also serves a key role in promoting AG in neoplastic tumor cells (Herranz and Cohen, 2017; Eichenlaub et al, 2018; Wang et al, 2016). Therefore, our studies of fly macrophages provide a new in vivo system in which we can study how Hif1α promotes cell activity by modulating central carbon metabolism.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The role of Hif1α in regulating this switch is of significant interest because, although this transcription factor is classically associated with the response to hypoxia, our study adds to the growing list of examples in which Hif1α remodels cellular metabolism in the context of cell proliferation, activation, and competition, even under normoxic conditions (Miyazawa and Aulehla, 2018). Moreover, our finding is particularly intriguing in light of the fact that Hif1α also serves a key role in promoting AG in neoplastic tumor cells (Herranz and Cohen, 2017; Eichenlaub et al, 2018; Wang et al, 2016). Therefore, our studies of fly macrophages provide a new in vivo system in which we can study how Hif1α promotes cell activity by modulating central carbon metabolism.…”
Section: Discussionmentioning
confidence: 91%
“…Since Hif1α can induce AG in both murine and Drosophila cells (Peyssonnaux et al, 2007; Herranz and Cohen, 2017; Eichenlaub et al, 2018), we examined the possibility that this transcription factor also promotes glucose catabolism within activated macrophages. Although Hif1α is known to be expressed continuously in almost all tissues and regulated predominantly at the post-translational level, we observed that Hif1α mRNA was significantly elevated in APMФs (Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drosophila has proven to be a powerful genetic model organism for studying tumorigenesis in vivo largely due to high conservation of genes and signaling cascades between human and flies and reduced genetic redundancy (Gonzalez, 2013; Herranz and Cohen, 2017) (Supplementary file 1). In a recent study, we showed that elevation of Drosophila Hipk causes an in vivo tumor model characterized by tissue overgrowth, loss of epithelial integrity and invasion-like behaviors (Blaquiere et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The core metabolic pathways that regulate energy homeostasis are highly evolutionarily conserved, and the fruit fly Drosophila melanogaster has served as an excellent model for metabolic and diet-associated diseases (reviewed in [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]). For example, flies have been used to investigate the metabolic control of tissue growth, and the link between the energy metabolism and cancer [ 18 ]. Drosophila has also been used to model obesity induced by high-sugar (HSD) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] and high-fat diets (HFD) [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%